(untitled) (Namn och konflikter: Handlingar från NORNA:s 50:e symposium i Uppsala den 14–16 november 2023, 2025)
This article tackles the issue of the disappearance of a first name. When can a name be considered to have disappeared? The basic data used in the study is taken partly from the “Norstedt data” presented by Sture Allén and Staffan Wåhlin in Förnamnsboken in 1995, partly from Statistics Sweden. The frequency change of almost 50 first names between the end of the 19th century and 2022, except for the years 1995–1997, is analyzed and discussed in the article. The results show that it is difficult to find names in Sweden that have